Autism spectrum disorder and vitamin D status: A cross-sectional study of children in a developing country in Southeast Asia. (June 2021) - Jayanath, Subhashini; Fong, Choong Yi; Sarvananthan, Rajini
Highlights: First Southeast Asian study of prevalence of vitamin D deficiency in children with autism spectrum disorder. Demonstrates a statistically significant association between female gender and vitamin D deficiency. Highlights improvement in autism spectrum disorder severity following treatment of vitamin D deficiency. Absence of improvement in parent-reported behavioural symptoms with vitamin D deficiency treatment. Abstract: Background: Determine the prevalence and risk factors of vitamin D deficiency (<35 nmol/L) in children with autism spectrum disorder (ASD); and explore the association between vitamin D deficiency with ASD severity and behavioural symptoms. Method: Cross-sectional study of children with ASD at a tertiary hospital. Children with vitamin D deficiency (<35.0 nmol/L) were treated (1200IU cholecalciferol, daily for 3 months). ASD severity was determined via the Childhood Autism Rating Scale, 2nd Edition (CARS-2); and behavioural symptoms via the Aberrant Behaviour Checklist, 2nd Edition (ABC-2). Scores were compared between the vitamin D deficient and non-deficient groups. Results: There were 103 participants (85.4 % male). Mean age: 6.2 years (SD = 2.4), 19 % were vitamin D deficient and 42 % were insufficient. Mean vitamin D concentration was 45.8 nmol/L (SD = 13.5). Female gender was significantly associated with vitamin D deficiency (OR 5.05, 95 % CI: 1.56, 16.31, p = 0.007). Post-vitamin D treatment, there was a significant reduction in CARS-2 scores (p < 0.05), but not ABC-2 scores. Conclusions: Nearly two-thirds (61 %) of Malaysian children with ASD have vitamin D deficiency (19 %) and insufficiency (42 %). Vitamin D treatment among vitamin D deficient children with ASD resulted in improvement in ASD symptom severity but not behavioural symptoms.